A Study of Synoptic Conditions Associated with Spring Dust Storms in Jordan - Ghanem, Ali; Khalil, Yousef (Dirasat: Human and Social Sciences, 2021)
A Study of Synoptic Conditions Associated with Spring Dust Storms in Jordan. This research aims to study the synoptic conditions associated with spring’s dust storms (visibility 0-1 km) in Jordan during the study period 1980-2016. There is a large annual variation of dust storms (DS), the coefficient of variation is 75%, with annual average of 7.5. The largest numbers of the dust storms occurred in 2003, and there was no record of any dust storm in 1983. Dust storms form when strong winds blow from dry soil in the desert (eastern and southern Jordan), and cause increasing temperature and decreasing humidity The analysis of surface weather maps for dust storms events revealed that most of (DS) were associated with cold fronts (104) DS, the number of DS decreased to (84) DS associated with Khamasine depressions, and to (43) DS with the Red sea low. Most dust storms (122) DS occurred in April (122) DS, and the others were divided between March (89) DS and May (86) DS.